Helicobacter pylori infection and its related factors in junior high school students in Nagano Prefecture, Japan. Issue 2 (27th October 2016) - Nakayama, Yoshiko; Lin, Yingsong; Hongo, Minoru; Hidaka, Hiroya; Kikuchi, Shogo
Abstract: Background: There have been few reports on Helicobacter pylori (H. pylori) infection in asymptomatic Japanese children and adolescents. We hypothesized that the prevalence of H. pylori infection is very low among Japanese children and that clinical variables such as serum pepsinogen and iron levels are associated with H. pylori infection. Materials and Methods: We conducted a cross‐sectional analysis of a sample of 454 junior high school students aged 12‐15 years in four areas in Nagano Prefecture. A commercial ELISA kit (E‐plate Eiken H. pylori antibody) was used to measure IgG antibody against H. pylori . Serum pepsinogen and iron levels were also measured using standard methods. A urea breath test was performed for seropositive students. Results: The overall prevalence of H. pylori was 3.1% (14/454). There were no significant differences in H. pylori prevalence among mountain, rural, and urban areas. The mean level of both serum pepsinogen (PG I) and PG II was significantly increased in the seropositive subjects compared with the seronegative subjects. When the cutoff values for adults (PG I: 70 ng/mL and PG I/II ratio: 3) were used, 4 of 14 subjects had PG I ≤70 ng/mL and PG I/II ratio ≤3. The results of a logistic regression analysis showed that low serum iron levels were significantly associated with H. pylori infection ( P =.02). Conclusions: The prevalence of H. pylori infection is as low as 3% among junior high school students aged 12‐15 years in Japan. The disappearance of H. pylori is accelerating in Japanese children.